Youth self-report of emotional maltreatment: Concordance with official reports and relation to outcomes. (March 2016) - White, Catherine Roller; English, Diana; Thompson, Richard; Roberts, Yvonne Humenay
Abstract: Emotional maltreatment (EMT) is an underreported, common, and pernicious type of maltreatment with long-lasting negative consequences. This paper examines concordance between youth self-report of EMT and official reports using data from 770 participants in the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN). In addition, the paper examines the relation between the experience of EMT in childhood (as measured both through self-report at ages 12 and 16, and in official reports throughout childhood) and trauma symptoms and risk behaviors in young adulthood (measured at age 18). The correlation between self-reported experiences of EMT and official reports was very low, ranging from 0.05 to 0.12 across the four EMT subtypes ( psychological safety and security ; acceptance and self-esteem ; autonomy ; and restriction ). Controlling for race, gender, and official reports of other types of maltreatment, both youth self-report and official reports of the psychological safety and security subtype of EMT predicted trauma symptoms, including anger, anxiety, depression, intrusive experiences, defensive avoidance, and dissociation. Improved detection of EMT and more effective and targeted interventions are needed, both to decrease rates of EMT from caregivers and to assuage its harmful effects on children and youth. Highlights: Emotional maltreatment (EMT) receives relatively little attention compared to other types of maltreatment. Exposure to EMT is related to increased trauma symptoms and risky behaviors. Both youth self-report and official reports of the psychological safety and security subtype of EMT predicted trauma symptoms. The correlation between self-reported experiences of EMT and official reports was very low. Improved detection of EMT and more effective and targeted interventions are needed.